Manual for Preclinical Removable Prosthodontics: Removable Partial Dentures Instructor's Guide - Marjan Moghadam; Bijan Moghadam; Leila Jahangiri (Association of American Medical Colleges, 2011)
Abstract The module includes a manual for preclinical removable prosthodontics that features includes step-by-step instructions with color photographs of procedures involved in making removable partial dentures. The purpose of this resource is to guide clinicians and dental practitioners through the steps involved in the fabrication of removable partial dentures as illustrated through preclinical laboratory exercises. Each chapter includes specific education objectives and clinically relevant discussion points to guide instructors in the didactic process, as well as many pictures to guide students in the laboratory process. This manual is the main text/information guide for the preclinical laboratory sessions at the New York University College of Dentistry. It is also being utilized as a review for clinic students in treatment of patients as well as for standardization of faculty.